ChemInform Abstract: Cyclization of (2‐Alkenylphenyl)carbonyl Compounds to Polycyclic Arenes Catalyzed by Copper(II) Trifluoromethanesulfonate or Trifluoromethanesulfuric Acid. Issue 9 (5th March 2013) - Liu, Wei‐Min; Tnay, Ya Lin; Gan, Kian Ping; Liu, Zhen‐Hong; Tyan, Wan Huei; Narasaka, Koichi
Abstract Various polycyclic arenes are efficiently synthesized using different (alkenylphenyl)carbonyl compounds as starting materials.